2011
DOI: 10.1590/s0103-84782011005000105
|View full text |Cite
|
Sign up to set email alerts
|

Suscetibilidade de Rhipicephalus (Boophilus) microplus a carrapaticidas em Mato Grosso do Sul, Brasil

Abstract: O carrapato bovino, Rhipicephalus (Boophilus) microplus, destaca-se dentre os ectoparasitas de importância econômica à pecuária nacional, tornando-se necessária a adoção de medidas de controle, particularmente em rebanhos Bos taurus e seus cruzamentos. O controle do carrapato tem sido cada vez mais difícil devido à constatação de populações resistentes aos diversos produtos em uso. Neste estudo, teve-se por objetivo conhecer a suscetibilidade desse carrapato a acaricidas em Mato Grosso do Sul. De outubro de 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
26
1
9

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(44 citation statements)
references
References 9 publications
8
26
1
9
Order By: Relevance
“…microplus specimens from the states of São Paulo, Ceará, Minas Gerais and on many properties in Mato Grosso do Sul (Tables 2 and 3), with these products exhibiting efficacy ranging from zero to 100% for the three analyzed active ingredients (alpha-cypermethrin, cypermethrin and deltamethrin). These results confirmed the results obtained by Koller et al (2009), Gomes et al (2011) and Mendes et al (2013) in Mato Grosso do Sul and those obtained by Mendes et al (2001Mendes et al ( , 2011 and Pereira (2006) in the state of São Paulo. There are no reports of such resistance in Ceará (HIGA et al, 2015), but it has been reported in other states in the northeastern region of Brazil, including Bahia (CAMPOS & OLIVEIRA, 2005;RAYNAL et al, 2013) and Pernambuco (SILVA et al, 2005).…”
Section: Pyrethroidssupporting
confidence: 92%
See 2 more Smart Citations
“…microplus specimens from the states of São Paulo, Ceará, Minas Gerais and on many properties in Mato Grosso do Sul (Tables 2 and 3), with these products exhibiting efficacy ranging from zero to 100% for the three analyzed active ingredients (alpha-cypermethrin, cypermethrin and deltamethrin). These results confirmed the results obtained by Koller et al (2009), Gomes et al (2011) and Mendes et al (2013) in Mato Grosso do Sul and those obtained by Mendes et al (2001Mendes et al ( , 2011 and Pereira (2006) in the state of São Paulo. There are no reports of such resistance in Ceará (HIGA et al, 2015), but it has been reported in other states in the northeastern region of Brazil, including Bahia (CAMPOS & OLIVEIRA, 2005;RAYNAL et al, 2013) and Pernambuco (SILVA et al, 2005).…”
Section: Pyrethroidssupporting
confidence: 92%
“…microplus specimens from 6 of the 24 (25%) properties evaluated, with an average efficacy of 88.13%. These data confirmed the results of Koller et al (2009) and Gomes et al (2011), who also tested this product using the "Adult Immersion Test" and found unsatisfactory average efficacies of 85.64% and 85.28%, respectively.…”
Section: Organophosphatessupporting
confidence: 89%
See 1 more Smart Citation
“…However, the indiscriminate use of these substances has been conducted to the appearance of several cases of tick resistance (Arantes et al, 1995). This phenomenon has been widely reported (Li et al, 2004;Rosado-Aguilar et al, 2008), including various descriptions in Brazil (Campos Júnior;Oliveira, 2005;Gomes et al, 2011), where there are reports in Rio Grande do Sul (Patarroyo;Costa, 1980), Minas Gerais, Espírito Santo (Leite et al, 1995), São Paulo (Soares et al, 2001), Bahia and Pernambuco (Santana et al, 2013).…”
Section: Introductionmentioning
confidence: 86%
“…(B.) microplus to almost every chemical group in Mato Grosso do Sul State has been demonstrated; this situation is detrimental to Brazil as a whole (GOMES et al, 2011) and affects several other countries (FAO, 2004). Due to this reduction in the susceptibility to current acaricidals, there has been an increase in the development of studies using natural products to search for new active ingredients (NEEWMAN;CRAGG, 2012).…”
Section: Introductionmentioning
confidence: 99%